Cultural entrepreneurship: A review of the literature - Nevena Dobreva; Stanislav Ivanov (Tourism & Management Studies)
The paper provides a comprehensive review of Scopus-indexed English language publications on entrepreneurship in cultural and creative industries and the arts. The paper analyses 131 publications published in the period 1982 – 2019 through quantitative analysis of frequencies and cross-tables, and qualitative thematic analysis of the publications. Eight research domains were identified: ‘Characteristics and motivation of entrepreneurs’, ‘Business models’, ‘Audience development’, ‘Use of information and communication technologies’, ‘Urban development’, ‘Public policy’, ‘Incubators and clusters’ and ‘Entrepreneurial education’. Findings show that two-thirds of the papers are based on empirical research, most of which is conducted in the UK. From a managerial perspective, conclusions are that the cultural entrepreneur is gradually becoming a central figure in contemporary cultural processes who has the potential to fulfill the market and audience needs, fill the emerging business niches and contribute to the revitalization of cities and regions. It identifies research gaps and formulates directions for future research.